Evaluación del Apantallamiento Electromagnético del Concreto a partir de Simulaciones en Alta Frecuencia y la Aplicación del modelo de Jonscher - Granados Vivas, Camilo Alejandro; Cubides, Herbert Enrique Rojas; Santamaria Piedrahita, Francisco (Ingeniería, 2020)
Context: This paper analyzes the effectiveness of electromagnetic shielding of several concrete structures based on the variation of the thickness and the content or level of humidity (NH) for a defined frequency range. Method: The study is based on the implementation of simulations in two dimensions (2D) using a software based on the finite element method (FEM) and it was developed from a set of values obtained from the application of mathematical models for dielectric media. Initially, the complex electrical properties of the structures (dielectric permittivity and conductivity) are characterized by applying the Jonscher´s mathematical model of three variables. Subsequently, these properties are evaluated with different concrete structures for a specific frequency range. Results: It is observed that the electromagnetic shielding offered by the concrete increases when the NH and the thickness of the structures are increased. Additionally, the evidencesshow that energy losses due to absorption are greater compared to the other types of losses analyzed in the study Conclusions: After the investigation, it can be affirmed that the Jonscher electromagnetic model offers a good response when it is applied to the complex electrical properties of concrete in a frequency range from 250 MHz up to 700 MHz. Also, by varying the thickness and the humidity level in the structures analyzed, an increase in the effectiveness of the total electromagnetic shielding was evidenced. Because concrete is an imperfect dielectric medium, energy losses by reflection are low compared to absorption losses and losses due to multiple reflections. However, this structural material can be used as a natural shield against radiated electromagnetic disturbances in the UHF band. Acknowledgements: This work was made possible thanks to the support and advice of the Electromagnetic compatibility and interference research group (GCEM-UD) of the Universidad Distrital Francisco José de Caldas.